2016
DOI: 10.5750/ejpch.v4i2.1082
|View full text |Cite
|
Sign up to set email alerts
|

Improving patients experience in a neuro-rehabilitation unit using tablet computers

Abstract: Rationale, aims and objectives: Patients in stroke rehabilitation units spend considerable time unengaged in therapeutic or meaningful activity, feeling bored with suboptimal engagement in rehabilitation. Systematic reviews have shown that novel interventions such as interactive video gaming result in improved motor function and cognitive performance. The objective of this study was to evaluate the feasibility of introducing “tablet computers - iPads” in hospital rehabilitation programmes and their impact on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Utilising tablet computers therefore has the potential to reduce social isolation and might prove to be cost-effective by reducing length of hospital stay and servicesdependency. Feedback from rehabilitation therapists in our recent service evaluation study indicated enhanced patients' participation and engagement in therapy sessions with the use of tablet computers [31]. Therapists also reported reduced levels of patients' abandonment of therapy sessions.…”
Section: Impact Of Ipad On Patients' Engagement Social Isolation Anmentioning
confidence: 93%
See 2 more Smart Citations
“…Utilising tablet computers therefore has the potential to reduce social isolation and might prove to be cost-effective by reducing length of hospital stay and servicesdependency. Feedback from rehabilitation therapists in our recent service evaluation study indicated enhanced patients' participation and engagement in therapy sessions with the use of tablet computers [31]. Therapists also reported reduced levels of patients' abandonment of therapy sessions.…”
Section: Impact Of Ipad On Patients' Engagement Social Isolation Anmentioning
confidence: 93%
“…In addition to improving functional recovery, several qualitative data demonstrates high acceptance and satisfaction of iPad-based rehabilitation programmes by stroke survivors [27][28][29][30][31]50]. Qualitative data presented by White et al (2014) from 12 stroke survivors investigated stroke survivors' acceptability of iPad-based rehabilitation in the first 3 months of recovery [30].…”
Section: Patients' Acceptability Of Ipad-based Rehabilitation and Selmentioning
confidence: 99%
See 1 more Smart Citation
“…Main priority for applications designed for the stroke patient population is the simplicity of use, technical support and foolproof content [36]. Our data shows that at a patient level use of tablet technologies is acceptable and feasible as long as they are easy to use and beneficial at an individual level [37]. Users of the application had positive feedback on the layout of the interface and Chatbot design.…”
Section: Feedback Of Progressmentioning
confidence: 86%
“…Some participants acknowledged that the Chatbot design helps to create a feeling of real conversation and someone supporting them. Reduced feeling of loneliness and abondominet increases engagement and reduces feelings of isolation and boredom [37]. Another factor that increases engagement is patents ability to monitor their progress and have access to educational information [38].…”
Section: Feedback Of Progressmentioning
confidence: 99%